Sperm transfer through hyper-elongated beetle penises – morphology and theoretical approaches - Matsumura, Yoko (Sci Rep, 2019)
Many insects possess a hyper-elongated intromittent organ with a diameter of only a few micrometers. Using morphological and theoretical approaches, we investigated the biomechanics of sperm transfer through such organs by calculating (1) how far and how fast sperm could fill in the penis by capillary action, (2) how much capillary pressure is generated in the penis, and (3) how much pressure is needed to pump sperm out of the penis. The results enabled us to propose the following hypotheses: (1) penile filling basically occurs by capillary action, and (2) sperm transport to females occurs by contracting the sperm pump muscles or by active propulsion of spermatozoa. Potential experimental approaches to test these hypotheses are discussed.